"I'm prepared for this moment": The role of mindfulness in the psychosocial health of women of color. Issue 1 (8th June 2022) - Sebastian, Bini B.; Slaten, Christopher D.
Abstract: This study utilized a phenomenological approach to explore how women of color ( N = 7) engage in mindfulness practices to improve their psychosocial well‐being, specifically as it relates to identity development and belongingness. Five themes emerged: awareness of mind–body connection, resilience in the face of discrimination, empathic perspective‐taking, awareness of internalized biases, and global sense of belonging. Implications for counselors and future research are discussed. Resumen: Este estudio utilizó un enfoque fenomenológico para explorar cómo las mujeres de color ( N = 7) practican la atención plena para mejorar su bienestar psicosocial, en concreto en cuanto a su relación con el desarrollo de la identidad y el sentimiento de pertenencia. Surgieron cinco temas: conciencia de la conexión entre el cuerpo y la mente, resiliencia frente a la discriminación, adopción de perspectivas empáticas, conciencia de los sesgos interiorizados y un sentimiento global de pertenencia. Se discuten las implicaciones para consejeros e investigaciones futuras.